Akuntansi Pertanggungjawaban Sosial Menggugat Keuangan Perusahaan Ditinjau Dari Konsep Going Concern - Saiful Muchlis; Mariyani Mariyani (LPPM ISNJ Bengkalis, 2021)
The purpose of this study is to find out the application of the going concern concept combined with financial performance to be able to encourage companies to carry out their social responsibility to remain a sustainable (future) point. In addition, this study also aims to determine the perceptions and level of satisfaction felt by stakeholders on the implementation of corporate social responsibility (CSR) programs carried out by the company to stakeholders in order to guarantee the company's business continuity in the future. This research is qualitative research with a critical approach based on pseudo sustainability through interviews with a total of 6 informants. The results showed that analyzing the company's finances in combination with the going concern concept was able to encourage companies to carry out their social responsibility to remain a concern for the future. The results of the study also show that the CSR programs carried out by the company are considered good and very beneficial for employees and the community around the company. This research also shows that the evaluation of the implementation of CSR programs is realized quite well, stakeholders both internal (employees) and external (local communities) are quite satisfied with the implementation of CSR programs carried out by the company to stakeholders.